Harmful association of sprinting with muscle injury occurrence in professional soccer match-play: A two-season, league wide exploratory investigation from the Qatar Stars League. Issue 2 (February 2020) - Gregson, Warren; Di Salvo, Valter; Varley, Matthew C.; Modonutti, Mattia; Belli, Andrea; Chamari, Karim; Weston, Matthew; Lolli, Lorenzo; Eirale, Cristiano
Abstract: Objectives: To investigate the impact of physical efforts performed in the period preceding activity as a potential risk factor of muscle injury during match-play within a sample of professional soccer players. Design: Observational cohort study. Methods: Match load (running [>14.4–19.8 km/h], high-speed running [>19.8–25.2 km/h], sprinting [>25.2 km/h], leading and explosive sprint type) averaged in 1-min and 5-min periods prior to an event or non event for 29 professional outfield soccer players. Conditional logistic and Poisson regression models estimated the relationship between load and injury for a 2 within-subject standard deviation in match load or 1-action increment in the number of sprinting activities, respectively. Associations were deemed beneficial or harmful based on non-overlap of the 95% confidence intervals against thresholds of 0.90 and 1.11, respectively. Results: An increment in sprinting distance [+2-SDs = 11 m] covered over a 1-min period (odds ratio [OR]: 1.22, 95%CI, 1.12 to 1.33) increased the odds of muscle injury. Conclusions: Our study provides novel exploratory evidence that the volume of sprinting during competitive soccer match-play has a harmful association with muscle injury occurrence.